AAV-mediated pancreatic overexpression of Igf1 counteracts progression to autoimmune diabetes in mice - Cristina Mallol; Estefania Casana; Veronica Jimenez; Alba Casellas; Virginia Haurigot; Claudia Jambrina; Victor Sacristan; Meritxell Morró; Judith Agudo; Laia Vilà; Fatima Bosch (Elsevier, 2017)
Objective: Type 1 diabetes is characterized by autoimmune destruction of β-cells leading to severe insulin deficiency. Although many improvements have been made in recent years, exogenous insulin therapy is still imperfect; new therapeutic approaches, focusing on preserving/expanding β-cell mass and/or blocking the autoimmune process that destroys islets, should be developed. The main objective of this work was to test in non-obese diabetic (NOD) mice, which spontaneously develop autoimmune diabetes, the effects of local expression of Insulin-like growth factor 1 (IGF1), a potent mitogenic and pro-survival factor for β-cells with immunomodulatory properties. Methods: Transgenic NOD mice overexpressing IGF1 specifically in β-cells (NOD-IGF1) were generated and phenotyped. In addition, miRT-containing, IGF1-encoding adeno-associated viruses (AAV) of serotype 8 (AAV8-IGF1-dmiRT) were produced and administered to 4- or 11-week-old non-transgenic NOD females through intraductal delivery. Several histological, immunological, and metabolic parameters were measured to monitor disease over a period of 28-30 weeks. Results: In transgenic mice, local IGF1 expression led to long-term suppression of diabetes onset and robust protection of β-cell mass from the autoimmune insult. AAV-mediated pancreatic-specific overexpression of IGF1 in adult animals also dramatically reduced diabetes incidence, both when vectors were delivered before pathology onset or once insulitis was established. Transgenic NOD-IGF1 and AAV8-IGF1-dmiRT-treated NOD animals had much less islet infiltration than controls, preserved β-cell mass, and normal insulinemia. Transgenic and AAV-treated islets showed less expression of antigen-presenting molecules, inflammatory cytokines, and chemokines important for tissue-specific homing of effector T cells, suggesting IGF1 modulated islet autoimmunity in NOD mice. Conclusions: Local expression of Igf1 by AAV-mediated gene transfer counteracts progression to diabetes in NOD mice. This study suggests a therapeutic strategy for autoimmune diabetes in humans.